2020
DOI: 10.1111/jch.14143
|View full text |Cite
|
Sign up to set email alerts
|

Prices of combination medicines and single‐molecule antihypertensive medicines in India's private health care sector

Abstract: More than half of patients with hypertension require two or more medicines to control blood pressure. Combinations of anti‐hypertensive medicines are available as Single Pill Combinations (SPCs) or Single Agent Pills (SAPs). SPCs of two or more anti‐hypertensive medicines facilitate simpler dosing schedules, decrease pill burden, increase adherence to medicine, and simplify procurement and distribution. Despite this, equivalent combinations of separate pills (SAPs) are often prescribed instead of SPCs under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Finally, using generic FDC of hypertension medications as opposed to combinations of single agent pills can reduce medication costs due to manufacturing or other efficiencies. A study of antihypertensives sold in the private sector in India demonstrated that the price of FDCs could be lower than their component single agent pills [ 24 ]. Similar price trends have been seen in HIV [ 25 ].…”
Section: An Ounce Of Preventionmentioning
confidence: 99%
“…Finally, using generic FDC of hypertension medications as opposed to combinations of single agent pills can reduce medication costs due to manufacturing or other efficiencies. A study of antihypertensives sold in the private sector in India demonstrated that the price of FDCs could be lower than their component single agent pills [ 24 ]. Similar price trends have been seen in HIV [ 25 ].…”
Section: An Ounce Of Preventionmentioning
confidence: 99%
“…However, Negi and colleagues identified that the price of SPCs was higher than the equivalent combinations of separate pills. 54 In India, 80 % of healthcare expenditure is borne by patients. 55 Therefore, SPCs related cost concerns need to be addressed on priority.…”
Section: Strategies To Improve Drug Adherencementioning
confidence: 99%
“…Automated BP monitors were available in only 10 per cent of the facilities, and low-cost antihypertensives and diabetes medications were unavailable in all primary care facilities 24 . Antihypertensive drugs are cheap and readily available in India 25 . However, forecasting, budgeting and appropriate distribution are required to ensure adequate availability in most peripheral health facilities 26 .…”
Section: Discussionmentioning
confidence: 99%